Dual antenna system for metal frame mobile phone applications. Issue 4 (24th December 2019) - Huang, Daiwei; Du, Zhengwei; Wang, Yan
Abstract: A dual antenna system with 77 mm × 10 mm × 7.5 mm for metal frame (MF) LTE/GPS mobile phones is proposed and studied. The antenna proposed in this study comprises two antenna elements (Ant 1 and Ant 2) and a decoupling line. Ant 1 as the main antenna that covers the lower band (698‐960 MHz), the GPS band, and the higher band (1710‐2690 MHz) consisting of a ground branch, a coupled line, and a tuning line. Ant 2 as the auxiliary antenna that covers the higher band consisting of a monopole branch and a match circuit. Ant 1 and Ant 2 form a two‐element MIMO antenna covering the higher band. The advantages of the proposed antenna are that the main antenna (Ant 1) covers the GPS band and all of the 2G/3G/4G bands, and the two‐element MIMO antenna covering the higher band, which consists of Ant 1 and Ant 2 located at the same side of a mobile phone with an MF, is obtained. A prototype is manufactured and tested. For Ant 1, the measured working bands (under −6 dB condition) are 685 to 965 MHz and 1480 to 2800 MHz, and the LTE700, GSM850, GSM900, GPS, GSM1800, GSM1900, UMTS, LTE2300, and LTE2500 bands are covered. For Ant 2, the measured working band (under −6 dB condition) is 1640 to 2720 MHz, and the GSM1800, GSM1900, UMTS, LTE2300, and LTE2500 bands are covered. The measured isolations between Ant 1 and Ant 2 are larger than 12 dB at the working bands. The measured efficiencies, envelope correlation coefficients, and mean effective gains are also presented.